Increases in the flux of carbon belowground stimulate nitrogen uptake and sustain the long-term enhancement of forest productivity under elevated CO2 - Drake, John E.; Gallet-Budynek, Anne; Hofmockel, Kirsten S.; Bernhardt, Emily S.; Billings, Sharon A.; Jackson, Robert B.; Johnsen, Kurt S.; Lichter, John; McCarthy, Heather R.; McCormack, M. Luke; Moore, David J. P.; Oren, Ram; et al. (Ecology letters, 2011)
Ecology Letters (2011) 14: 349–357 The earth’s future climate state is highly dependent upon changes in terrestrial C storage in response to rising concentrations of atmospheric CO2. Here we show that consistently enhanced rates of net primary production (NPP) are sustained by a C‐cascade through the root‐microbe‐soil system; increases in the flux of C belowground under elevated CO2 stimulated microbial activity, accelerated the rate of soil organic matter decomposition and stimulated tree uptake of N bound to this SOM. This process set into motion a positive feedback maintaining greater C gain under elevated CO2 as a result of increases in canopy N content and higher photosynthetic N‐use efficiency. The ecosystem‐level consequence of the enhanced requirement for N and the exchange of plant C for N belowground is the dominance of C storage in tree biomass but the preclusion of a large C sink in the soil.